A descriptive - contrastive analysis of English and Maguindanao consonants and vowels - Afdal, Eden (Gonzales) 1923- ([Quezon City publisher not identified], 1965)
This study identifies the problems encountered by the Maguindanao speaker learning the pronunciation of English consonants and vowels. A descriptive-contrastive analysis was made between Maguindanao and English consonant and vowel phonemes, their variants, and their distribution.
Thesis (Master of Arts in Teaching)--University of the Philippines.
Keywords: English language -- Study and teaching; Language and languages